A Assessment of natural radioactivity in gravel samples collected from Abidjan district in Côte d’Ivoire - AGBO, Alfred Djoman; Brigui, Jean-Claude Olkalé (European Journal of Applied Sciences, 2022)
Gravel is one of the reference materials used in the construction sector and in particular in Côte d’Ivoire. In this study, which appears to be one of the first works on construction materials in Côte d’Ivoire, radiological measurements are carried out on ten (10) samples of gravel from the district of Abidjan in order to evaluate the activity concentration of natural radionuclides (226Ra, 232Th and 40K). The measurements are made using the nuclear technique based on gamma spectrometry with a GeHP detector. The average activity concentrations in the samples were 5.98± 0.24 Bq.kg-1, 4.17± 1.65 Bq.kg-1 and 177.18± 3.50 Bq.kg-1 for 226Ra, 232Th and 40K respectively. These values, which were the first results obtained, show that the natural radioactivity in these gravels is comparable to what is usually measured in the same samples on a world scale, whose average limit values are 35 Bq.kg-1, 30 Bq.kg-1 and 400 Bq. kg-1 (UNSCEAR, 2000). Therefore, the radioactivity in these gravels does not pose an immediate health risk to the public. Long-term effects can be avoided by simple precautionary measures. Keywords : Gamma spectrometry Technique, gravel samples, District of Abidjan, activity concentration